Geopolitics of the Outer Space - Doboš, Bohumil. author. aut Link
IX, 138 p.
Keywords: This book presents a comprehensive geopolitical analysis of European space activities. By studying outer space as a physical and socio-economic space as well as a military-diplomatic area, the author helps readers understand outer space as a geopolitical environment. The book also offers insights into the behavior and strategies of different actors, with a special focus on the European space strategy and the nature of the European space program and diplomacy.